Business Finance Catalysts: Promotion, Sales, and Financial Management Tactics that Improve Company Financial Performance - Novita Rosanti (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study explores the relationship of promotion and sales strategies with firm financial performance in a comprehensive context. Quantitative methods were used to collect and analyze data from 120 companies in Indonesia. Using a purposive sampling technique, 420 respondents completed a questionnaire highlighting promotional strategy, sales, and financial performance. Variables such as promotional expenditure, creativity, and market responsiveness were measured through statistical analysis, including multiple regression. The findings show that factors such as promotion fund allocation, campaign innovation, product price management, distribution, and customer service play an important role in a company's financial success. This study provides an in-depth understanding of the importance of promotion and sales strategies in achieving optimal financial performance.